1989
DOI: 10.1007/bf00378951
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community structure driven by vertebrate and invertebrate predators

Abstract: A zooplankton community was established in outdoor experimental ponds, into which a vertebrate predator (topmouth gudgeon: Pseudorasbora parva) and/or an invertebrate predator (phantom midge larva: Chaoborus flavicans) were introduced and their predation effects on the zooplankton community structure were evaluated. In the ponds which had Chaoborus but not fish, small- and medium-sized cladocerans and calanoid copepods were eliminated while rotifers became abundant. A large-sized cladoceran Daphnia longispina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 50 publications
3
82
1
Order By: Relevance
“…Invertebrate predators, such as Chaoborus (Diptera) larvae, play a major role in structuring zooplankton communities in lakes by directly limiting prey populations (Hanazato & Yasuno 1989;Hanazato 1990) and altering the dynamics, size and structure of prey populations (Neill 1981;Mumm 1997;Riccardi et al 2002). The 'Chaoborus-Daphnia / predator-prey' system is very well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate predators, such as Chaoborus (Diptera) larvae, play a major role in structuring zooplankton communities in lakes by directly limiting prey populations (Hanazato & Yasuno 1989;Hanazato 1990) and altering the dynamics, size and structure of prey populations (Neill 1981;Mumm 1997;Riccardi et al 2002). The 'Chaoborus-Daphnia / predator-prey' system is very well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The size structure of Daphnia in Lake Piaseczno could be Vertebrates eat selectively large-sized zooplankters whilst invertebrates typically select small or medium-sized prey. Hanazato and Yasumo (1989) found that in ponds where vertebrate (topmouth gudgeon) and invertebrate predators (phantom midge larva) occurred, small and largesized cladocerans were scarcely found. A similar phenomenon was observed in Lake Piaseczno.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effect of both the kairomone and carbaryl (Table 4) reduced the population growth to half or less of that predicted from the separate effects of the two factors. Such a large reduction is particularly important to Daphnia, which typically requires a high rate of population growth to persist through periods of high mortality from predators (18,23,(48)(49)(50) (60); the more recent data are from samples taken by Dodson. by toxic xenobiotics may result in higher mortality due to both vertebrate and invertebrate predators. For example, an increase in swimming velocity will increase encounter rate with predators and therefore increase the rate of mortality (51).…”
Section: Ecological Consequences Morphology and Life Historymentioning
confidence: 99%